REVIVING AGRICULTURE SECTOR: AN INITIATIVE OF GOVERNMENT OF INDIA AMIDST COVID-19 - Shivani Solanki, Dr. Namrata Prakash ,Divya Punj, Emmanuel Elgin Gabriel (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The global health crisis due to COVID 19 is deepening economic distress which cannot be overlooked.The Indian government took prompt action since the pandemic created an unusual situation. This paper focuses attention on challenges faced by the Indian agricultural sector as a consequence of the crisis altogether highlighting the relief measures announced by the government to give a boost to thissector. The impetus is also on the support extended by the government in recent years to ensure that the farmers are not impacted by the downturn of the economic slowdown.The study throws light upon the situation of these sectors both before & after the outbreak of COVID 19and identify the steps taken by the government of India to uplift the agricultural sector through its Self-Reliant Indian Movementoffering a comprehensive package that will help overcome the crisis these sectors are going through and help the economy to revive.